AS DIFERENTES ABORDAGENS DO PROCESSO EDUCATIVO E SEUS REFLEXOS NO ENSINO DE ENFERMAGEM EM NÍVEL MÉDIO - Simone Shirasaki Orosco; Tereza de Jesus Ferreira Scheide (Universidade do Oeste Paulista, 2008)
This study has the objective to reflect on nursing education in medium level in times of changes in the education and in the modern society.The education of nursing in this level has been one of that it faces greater in recent years difficulty in relation its conception, structure and organization. In spite of the great number of schools of medium education of nursing in the country, researches about these professionals, their formation needs and job market are still scarce. Many teachers that act in this area, they don't attend courses of pedagogic training or master degree in the education to they begin their activities in the teaching. Like this, their educational practices still follow traditional models, taking the formation of professionals with characteristics of the biomedical-technicist model. When review historically the moments of the nursing education, it is really observed great periods that suffered influences of the traditional approach and technicist. However, with passing of the years, these paradigms demonstrate not to correspond to the current necessities, demanding reflections and debates on the problem, where the teacher has been fundamental paper in the search of a teaching-learning process based on freedom and necessary abilities to the current context.